Application of 3D printing photopolymerization technique in the fabrication of two-layered tablets - Adamov, Ivana; Tenić, Milica; Pešić, Nikola; Medarević, Djordje; Ivković, Branka; Ibrić, Svetlana (Archives of Pharmacy, 2022)
In recent years, introduction of modern technologies, such as 3D printing, has opened a new chapter and caused a paradigm shift from manufacturing of large-scale to small batches of medicines tailored accordingly to the specific needs of patients. The aim of this study was to formulate and fabricate two-layered tablets using digital light processing (DLP) technique, which utilizes light irradiation to create solid objects from photoreactive liquid resin in a layer-by-layer manner. Hydrochlorothiazide (HHT, 5%,w/w) and warfarin sodium (VRN, 5%,w/w) were selected as model drugs, commonly used together in the treatment of cardiovascular diseases. 3D printing process was initiated with 0.10% of photoinitiator, at a constant ratio of poly(ethylene glycol)diacrylate and poly(ethylene glycol) 400, 1:1, with the addition of water (10%,w/w). 3D tablets, with each of the active substances in a separate layer, 8.00 mm in diameter and 1.50 mm thick, as well as combined two-layered tablets with HHT and VRN in individual layers, were successfully printed with Wanhao D8 printer. Dissolution test results showed immediate, but incomplete release of VRN (81.47 ± 1.47%, after 45 min) from individual layers, while the release of HHT was prolonged and complete (98.17 ± 3.11%, after 8 h). Significantly slower and incomplete release of VRN and HHT from combined tablets was observed. The absence of interactions and the presence of a layered structure were confirmed. DLP technique has a potential to provide fast fabrication of combined tablets, while further optimization of formulation factors is necessary in order to achieve complete drug release.